Structural equation modeling for green technology system in environmental monitoring - Mukaddas Abbasovna Umarova; Abbas Abdupattaxovich Nabixodjayev; Barno Shukhratovna Akbarova; Munisa Jamoliddin qizi Xusnuddinova (BIO Web of Conferences)
The current situation of environmental sustainability efforts and the problems existing in the implementation of green technologies are proposed to achieve enhanced regulatory compliance, improved technological adoption, and strengthened organizational commitment. This paper aimed at understanding the connections between factors that impact the adoption and success of technologies in environmental sustainability efforts. To meet the increased data accuracy demands of environmental monitoring and decision-making, the capability of green technology-driven analytical models must improve. As this study’s methodology, the structural equation modeling (SEM) method in green technology system assessment combines the latent variable analysis method based on regulatory influence, technological readiness, and organizational sustainability commitment. The research results show that the constructed model can systematically analyze the interconnections between regulatory frameworks, technological adoption rates, environmental outcomes, and organizational sustainability commitment. Which are more positively correlated, more statistically significant, and more instrumental to achieving long-term environmental sustainability. Analyzing this trend in technological adaptation reveals that technological readiness has been the largest contributor to the successful implementation of eco-innovations, with regulatory frameworks and organizational commitment (e.g., leadership support and stakeholder involvement) leading the way, on the other hand economic efficiency considerations have faded in recent decades.